Ivan Mikhailovich Sechenov: A New Look at The History of Psychology - Inanç Bozkurt, Tubanur; Bozkurt, Uğur (Border Crossing, 2024)
The history of psychology has been shaped by the emergence of different ideas to understand human behavior and mental processes. These ideas, which date back to antiquity, have played an essential role in developing psychology as a scientific discipline over time. One of the crucial figures who played a role in this process is undoubtedly Sechenov. Sechenov’s endeavor to use methods similar to those of the natural sciences in psychology, as well as his work in this area, laid the foundations for the development of experimental psychology. He also drew attention to the importance of physiological processes in explaining mental actions and conducted various experiments. In addition, Sechenov’s views paved the way for the development of behaviorism. This is because objective psychology had developed significantly in Russia before the emergence of behaviorism under the leadership of Sechenov. His ideas influenced the work of John B. Watson, Vladimir Mikhailovich Bekhterev, and Ivan Petrovich Pavlov. The fact that Sechenov was a pioneer in psychology and made influential contributions to many fields makes him an influential name in the history of psychology. Unfortunately, Sechenov is not well-known to the masses. Therefore, the primary purpose of this study is to introduce and explain Sechenov, his works, and his contributions.